An efficient strategy for mining high utility itemsets. (10th March 2011) - Le, Bac; Nguyen, Huy; Vo, Bay
Methods for mining high utility itemsets from databases have been discussed widely in recent years. They mine itemsets having high utility from databases. Pruning candidates based on transaction-weighted utilisation value is a good method at all. In this paper, we develop a tree structure called WIT-tree, and use it in the proposed TWU-mining algorithm, an algorithm for improving the mining time and the search space. Using Diffset for fast computing transaction-weighted utilisation values and saving memory will be discussed. Experimental results show that proposed algorithms are more efficient.